Analisis Ekologi Pemerintahan Terhadap Partisipasi Dalam Pengelolaan Sampah Di Pesisir Pantai Kota Tanjungpinang - Dessy Ari Yanti; Sepwana Manda Efapras Tampubolon; Kania Riva Afrilia Putri Hariyadi (CV. ITTC INDONESIA, 2026)
The coastal area of Tanjungpinang City faces serious problems related to waste accumulation, with volumes reaching 1.5 tons per day in the waters and piles of non-organic waste up to 3.5 meters in the Senggarang Beach area. This study aims to analyze the ecology of governance in relation to community participation in waste management in the coastal area of Tanjungpinang City. The method used is descriptive qualitative with a literature study type, utilizing secondary data sources in the form of academic journals, scientific articles, regional regulations, and data from related institutions. The results of the study indicate that the coastal area of Tanjungpinang has high ecological vulnerability due to the pressure of human activities and limited waste management infrastructure. Although the government has relevant regulations, their implementation is still far from adequate. Community participation is only at the level of tokenism or pseudo-participation based on Arnstein's Ladder of Participation Theory. This study recommends a co-management model through the establishment of a Joint Coastal Governance Forum involving the government, beach traders, and local environmental communities as a solution for sustainable coastal waste management.